A Case of Successful Ablation of a Gastrophrenic Fistula with n-Butyl-2-Cyanoacrylate - Ashish Mahajan; G Rao; Gordon Lees; Richard Owen (Canadian Journal of Gastroenterology)
A 79-year-old woman with a fistula between a subphrenic abscess and the fundus of the stomach was successfully treated with n-Butyl-2-Cyanoacrylate. Conservative management had failed. Clinical presentation, treatment progress and imaging findings by computed tomography scan, ultrasound, gastroscopy and fluoroscopy are presented, along with a brief review of the relevant literature.